2003
DOI: 10.1016/s0002-9440(10)64277-0
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Deficiency Accelerates Progression of Glomerulosclerosis in Susceptible Mice

Abstract: Estrogen deficiency may contribute to the development and progression of glomerulosclerosis in postmenopausal women. The responsiveness to estrogens could be controlled by genetic traits related to those that determine the susceptibility to glomerular scarring. This study was undertaken to determine whether the intensity of the sclerotic response was modified by the estrogen status in sclerosis-prone ROP Os/؉ mice. Ovariectomized ROP Os/؉ mice developed more severe renal dysfunction and glomerulosclerosis than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
82
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(90 citation statements)
references
References 23 publications
8
82
0
Order By: Relevance
“…Furthermore, we show that the activities of MMP-9 and MMP-2 are increased with E 2 replacement, suggesting that E 2 promotes ECM degradation. Our findings support previous studies, which have reported a similar renoprotective role of estrogen in sclerosis-prone mice (26), in the remnant kidney model (45), and in cultured mesangial cells (27) via similar mechanisms. It will be interesting in future studies to also examine the role of testosterone, as some studies indicate that it is not only the estrogen-deficient state that affects renal disease progression but also the change in ratio of estrogen to testosterone after estrogen deficiency (46).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, we show that the activities of MMP-9 and MMP-2 are increased with E 2 replacement, suggesting that E 2 promotes ECM degradation. Our findings support previous studies, which have reported a similar renoprotective role of estrogen in sclerosis-prone mice (26), in the remnant kidney model (45), and in cultured mesangial cells (27) via similar mechanisms. It will be interesting in future studies to also examine the role of testosterone, as some studies indicate that it is not only the estrogen-deficient state that affects renal disease progression but also the change in ratio of estrogen to testosterone after estrogen deficiency (46).…”
Section: Discussionsupporting
confidence: 92%
“…The age-related changes in BP in this animal thus correlate with the changes in renal pathology, suggesting that the renoprotective effects of E 2 replacement may be mediated via its effects on BP. However, several studies suggest that estrogens exert a renoprotective effect independently of their BP-lowering effects (3,26) by reducing cell death by apoptosis and increasing ECM degradation. Studies in this laboratory have shown that, in a STZ model of diabetes, E 2 replacement reduces renal collagen type IV synthesis and tubulointerstitial fibrosis without an effect on BP (53).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In both the diabetic and nondiabetic kidney, E 2 attenuates glomerulosclerosis and tubulointerstitial fibrosis by reducing synthesis of type I and type IV collagen, increasing expression of matrix metalloproteinases, and inhibiting apoptosis. 60,61,[68][69][70] Furthermore, E 2 decreases the expression of transforming growth factor-β, angiotensin AT1 receptor and endothelin-1, all of which stimulate abnormal cell growth and extracellular matrix metabolism and contribute to the vascular dysfunction associated with renal disease. 60,71-74 E 2 has also been shown to upregulate nitric oxide synthase activity and vascular endothelial growth factor expression in the glomerulus.…”
Section: Mechanisms Of Action Of Estrogens In the Kidneymentioning
confidence: 99%
“…6 -8 Female ROP Os/ϩ mice develop GS during their reproductive period of life and are, therefore, considered sclerosis-prone. 9 However, estrogen deficiency, induced by ovariectomy, accelerates glomerular dysfunction and scarring in young ROP Os/ϩ mice. 9 This suggests that endogenous estrogens only partially protect this mouse strain from the development of GS.…”
mentioning
confidence: 99%